Schaffer v. Weast's Effects on California Special Education Hearing Decisions. (September 2022) - Itkonen, Tiina; Tomlin, Bryan; Correia, Manuel G.; Sanchez, Luis A.; Schneider, Tracie; Kooker, Kellie
This research examined the associations between Schaffer v. Weast (2005) and special education due process hearing decisions in California. Using a database we coded from the state's due process hearings for cases that reached a decision (years 1995–2019), this study analyzed (1) how legal representation and the filing party affected the probability of the student fully or partially prevailing in these cases, and (2) how Schaffer affected student representation and the prevailing party before and after this ruling. The results indicate that while students were statistically as likely to be plaintiffs and/or represented by an attorney before and after the 2005 time break in the study, the decision raised the bar for students as the likelihood of favorable outcomes for students fell significantly in the wake of the ruling.